The surface morphology characterization of electroless nickel immersion gold under bump metallurgy (UBM) using SEM - Mohd Khairuddin, Md Arshad; Mohd Nazrin, Md Isa; Sohiful Anuar, Zainol Murad (American Institute of Physics, 2009)
Link to publisher's homepage at http://link.aip.org/link/?APCPCS/909/118/1